2019
DOI: 10.3390/app9071494
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Dimension Differentiation between Benign and Malignant Thyroid Nodules from Ultrasonography

Abstract: Recently, there is increasing interest in identifying benign and malignant nodules by using ultrasound diagnostic technology, which should be helpful to release patients with benign thyroid nodules from suffering unnecessary needle biopsy. In this work, fractal analysis was investigated for the capability of differentiating benign from malignant thyroid nodules during ultrasonography. The B-mode images for 57 patients with suspicious thyroid nodules were captured, followed by ultrasound-guided needle aspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…[ 12 13 14 ] The most common method of texture analysis is fractal dimension and FD values are consistently higher in malignant regions. [ 15 16 17 ] Recently Metze et al . [ 18 ] reviewed the role fractal dimension and found that FD increases in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 13 14 ] The most common method of texture analysis is fractal dimension and FD values are consistently higher in malignant regions. [ 15 16 17 ] Recently Metze et al . [ 18 ] reviewed the role fractal dimension and found that FD increases in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FD has been used for the classification of breast tumors,[ 19 ] in therapeutic response of small cell lung cancer[ 20 ] and to differentiate benign and malignant thyroid nodule. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…The usage of global fractal analysis at greyscale level in pathology detection is proven, with the ability among others to distinguish between benign and malignant tumours [39], toxicology research in fish [40], and small vessel disease in the eyes [41]. The homogeneity of our healthy volunteers may produce consistent FD values between huffaz and nonhuffaz, resulting in no significant difference detected by the statistical analysis of the two-sample t-test conducted.…”
Section: Global Greyscale Analysismentioning
confidence: 90%